CLUSTER ANALYSIS OF POVERTY, OPEN UNEMPLOYMENT AND EDUCATION PERCENTAGE IN CENTRAL JAVA FOR THE 2020 PERIOD - Anifa, Anis Sukha (Jurnal Ekonomi Balance, 2021)
This study aims to categorize districts/cities in Central Java Province based on cluster analysis of poverty, open unemployment and education level. The population and sample used in this study are 35 districts/cities in Central Java Province in 2020. The research data was taken from BPS secondary data. Data were analyzed using SPSS application with k-means cluster analysis. The results of this study explain that 35 regencies/cities in Central Java Province are divided into 2 clusters. The characteristics of cluster 1 have values above the average for the variables of poverty and education, but the open unemployment rate is below the average. The characteristics of cluster 2 have values above the average for the open unemployment rate variable, but the poverty and education variables have values below the average. Cluster 1 consists of districts Banyumas, Purbalingga, Banjarnegara, Kebumen, Purworejo, Wonosobo, Magelang, Boyolali, Klaten, Wonogiri, Karanganyar, Sragen, Grobogan, Blora, Rembang, Pati, Demak, Semarang, Temanggung, Pemalang and Brebes. Meanwhile, Cluster 2 consists of the districts of Cilacap, Sukoharjo, Kudus, Jepara, Kendal, Batang, Pekalongan, Tegal. In addition, there are also the cities of Magelang, Surakarta, Salatiga, Semarang, Pekalongan and Tegal.